Modeling the effects of cigarette smoke extract on influenza B virus infections in mice - Chavez, Jerald R.; Yao, Wangyuan; Dulin, Harrison; Castellanos, Jasmine; Xu, Duo; Hai, Rong (Frontiers in Immunology, 2023)
Influenza B virus (IBV) is a major respiratory viral pathogen. Due to a lack of pandemic potential for IBV, there is a lag in research on IBV pathology and immunological responses compared to IAV, including how certain environmental and lifestyle factors affect infection. Among them, cigarette smoking (CS) increases the risk and likelihood of worse disease outcomes caused by IAV infections. However, there is little to no information on how CS affects IBV infections, particularly in animal models. To this end, we developed an animal model system by pre-treating mice for two weeks with cigarette smoke extract (CSE), then infected them with IBV and monitored the resulting pathological, immunological, and virological effects. Our results reveal that the CSE treatment decreased IBV specific IgG levels yet did not change viral replication in the upper airway/the lung, and weight recovery post infection. However, higher concentrations of CSE did result in higher mortality post infection. Together, this suggests that CS induced inflammation coupled with IBV infection resulted in exacerbated disease outcome.